Benzodiazepine Usage, Healthcare Resource Utilization, and Costs Among Older Adults Treated with Common Insomnia Medications: A Retrospective Cohort Study - Wickwire EM; Juday TR; Gor D; Amari DT; Frech FH (Dove Medical Press, 2023)
Emerson M Wickwire,1,2 Timothy R Juday,3 Deval Gor,4 Diana T Amari,4 Feride H Frech3 1Sleep Disorders Center, Division of Pulmonary and Critical Care Medicine, Department of Medicine, University of Maryland School of Medicine, Baltimore, MD, USA; 2Department of Psychiatry, University of Maryland School of Medicine, Baltimore, MD, USA; 3Health Economics & Outcomes Research, US Medical Affairs, Eisai Inc., Nutley, NJ, USA; 4Real-World Evidence, Genesis Research, Hoboken, NJ, USACorrespondence: Timothy R Juday, Health Economics & Outcomes Research, US Medical Affairs, Eisai Inc, 200 Metro Blvd, Nutley, NJ, 07710, USA, Tel +1-551-502-2116, Email timothy_juday@eisai.comBackground: Benzodiazepines are commonly prescribed for insomnia management but are often associated with negative safety outcomes such as falls and abuse, particularly among older adults.Objective: The purpose of this real-world study was to compare the impact of benzodiazepines, low-dose trazodone, and zolpidem immediate release (IR) on healthcare resource utilization (HCRU), and costs among older adults (age ≥ 65 years) with insomnia in the US.Methods: Using the IBM MarketScan Medicare Supplemental Database, older adults with > 1 physician-assigned diagnosis of insomnia and treated with benzodiazepines were matched 1:1 on age, sex, and index-date to individuals treated with trazodone, and separately matched 1:1 on age and sex, to individuals treated with zolpidem immediate release (IR). Between-groups differences were analyzed using general linear models (GLMs) that controlled for multiple confounders.Results: Significant between-groups differences in HCRU and costs were observed such that relative to zolpidem IR and separately relative to low-dose trazodone, benzodiazepines were consistently associated with worsened outcomes.Conclusion: These findings build upon and extend prior knowledge on the negative impact of benzodiazepines and suggest directions for future research.Keywords: benzodiazepine, trazodone, zolpidem, elderly, insomnia, healthcare resource utilization, cost